Понятие информации. Часть 2. Функции научной теории - Кургаев, А.Ф. (Проблемы управления и информатики, 2020)
Усяка наукова теорія незалежно від специфіки знань і області формалізації повинна ефективно виконувати достатню кількість функцій обробки інформації. Для досягнення глобальної мети — максимальної допомоги у розв’язку кожної з нескінченної множини проблем еволюції суспільства — інформаційний комп’ютер має моделювати всі функції наукових теорій, об’єднані в концептуально єдину систему обробки знань, і за рахунок цього забезпечити можливість безпосередньо використовувати знання в явній формі для розв’язку поточних і нових проблем. Роз’яснено зміст комунікативних, дескриптивно-прескриптивних і аргументативных (дедукції, індукції, пояснення, передбачення, розуміння) функцій наукових теорій, описано моделі синтезу різних компонентів структури наукових теорій. Для організації досить складного діалогу суб’єкта із зовнішнім світом достатньо комунікативних функцій аналізу й породження мовних повідомлень і об’єктів дійсності. Дескриптивно-прескриптивні функції є основою пізнання й перетворення дійсності. Описовий характер мають усі факти дійсності, оцінювальний — стандарти, зразки, ідеали, норми. Аргументація є процес міркування, у ході якого породжуються докази (судження, умовиводи), що обґрунтовують оцінку (істинності або цінності) висловлення або теорії. Дано самоопис метамови нормальних форм знань. Наведено структуру ядра інформаційного комп’ютера, заснованого на цій метамові, у складі: компілятора метапрограм, двох інтерпретаторів (метапрограм і термінальних програм), глосарія термінів і двох масивів даних (вхідного й вихідного). Описано процес функціонування системи обробки знань на базі інформаційного комп’ютера. Наведено інформацію про реалізацію макета інформаційного комп’ютера у формі персонального комп’ютера, розширеного інтерпретатором баз знань, виконаним на макетній платі корпорації Actel, з мінімально необхідною апаратно-програмною підтримкою. Надання користувачам метамови для опису прикладних проблем і досконалої техно логії постановки й розв’язку задач, яка реалізує всі функції наукової теорії, забезпечить гранично високий ріст надійності «м’якого» продукту й ефективності програмування. Any scientific theory should effectively perform a variety of information processing functions, regardless of the specifics of knowledge and the field of formalization. To achieve the global aim — maximum assistance in solving each of the infinite number of problems of the evolution of society — the information computer should be able to simulate all the functions of scientific theories, which are combined into a conceptually single system of knowledge processing, and due to this the information computer should provide the possibility to use knowledge directly in an explicit form for solving current and new problems. The meaning of communicative, descriptive-prescriptive and argumentative (deduction, induction, explanation, prediction, understanding) functions of scientific theories is clarified. The models of synthesis of various components of the structure of scientific theories are described. The objects of real world and the communicative functions of analysis and generation of language messages are enough for the organization of arbitrarily complex dialogue between a subject and real world. The descriptive-prescriptive functions are the cornerstone for cognition and transformation of reality. All facts of reality are descriptive, whereas the standards, samples, ideals and norms are estimates. The argumentation is a process of reasoning during which the arguments, opinions and conclusions are generated, that justify the assessment of truth or falsity of a statement or a theory. The self-description of the meta-language of normal forms of knowledge is presented. The structure of the core of the information computer, which is based on this meta-language, is presented, comprised of the following: the meta-program compiler, two interpreters (the meta-program interpreter and the terminal program interpreter), a glossary of terms and two arrays of data (input array and output array). The process of functioning of a knowledge processing system based on an information computer is described. The information on the implementation of the layout of the information computer in the form of a personal computer supplemented with the knowledge base interpreter made on a prototyping board of Actel corporation using minimum required hardware and software support is given. Giving users the meta-language for describing application problems and the improved technology of formulating and solving problems, which realize all the features of a scientific theory, will provide extremely high growth of «soft» product reliability and programming efficiency.